Strengthening the Multi-Party Presidential Government in Indonesia - Hamudy, Moh. Ilham A.; Rifki, M. Saidi (Political Science Program, Universitas Negeri Semarang, 2019)
The Multi-Party Presidential Government in Indonesia has reached a critical point. The 2.5 percent parliamentary threshold rule in the 2009 Election was incapable to address the issue. The parliamentary threshold was raised to 3.5 percent in 2014, in the hope to reduce the number of party joining the election, but it failed to do so. There were 9 national parties participating in the 2009 election, and it will be increased to 16 in the 2019 election. Theoretically, the combination of multi-party parliament in a Presidential Government is rather strange. It is not surprising that the